Insulin resistance caused by lipotoxicity is related to oxidative stress and endoplasmic reticulum stress in LPL gene knockout heterozygous mice. Issue 1 (March 2015) - Li, Yang-Xue; Han, Ting-Ting; Liu, Yang; Zheng, Shuang; Zhang, Yao; Liu, Wei; Hu, Yao-Min
Abstract: Objective: To investigate the correlation of hypertriglyceridemia with abnormal glucose metabolism and insulin resistance. Methods: Lipid and glucose metabolism, whole-body and tissue-specific insulin sensitivity, genes and proteins related with oxidative stress and endoplasmic reticulum (ER) stress were compared between LPL+/− and control mice at different weeks of age. Results: 16–50-week LPL+/− mice had increased body weight compared with their respective controls. Fat mass in visceral adipose tissue (VAT) of 16 and 28-week LPL+/− mice were twice more than their control littermates, and 50-week LPL+/− mice showed the same trend of increase. Plasma lipids were higher in 16–50-week LPL+/− mice. 28- and 50-week LPL+/− mice had elevated tissue lipid accumulation (liver, skeletal muscle, pancreas) and impaired glucose tolerance, while 16-week LPL+/− mice showed no differences. Homeostasis model assessment of insulin resistance for 28 and 50-week LPL+/− mice were twofold greater, whereas that for 16-week LPL+/− mice had no change. Insulin-stimulated phosphorylated Akt (Ser473) in VAT of 28-week LPL+/− mice decreased by 80.6% (p = 0.001), and that in liver and skeletal muscle decreased by 62.4% (P < 0.001) and 51.8% (p = 0.005) respectively. Then we found that plasma malondialdehyde and reactive oxygen species levels in liver and skeletal muscle of LPL+/− mice were elevated. Increased ER stress biomarkers were also detected in liver and VAT of 28-week LPL+/− mice. Conclusions: Systemic LPL deletion results in impaired glucose tolerance, whole-body and tissue-specific insulin resistance, which is associated with tissue lipid deposition in various insulin target tissues. Furthermore, the activation of oxidative stress and ER stress may play an important role in the development of tissue-specific and systemic insulin resistance. Highlights: Systemic LPL deletion results in impaired glucose tolerance, whole-body and tissue-specific insulin resistance. The activation of oxidative stress and ER stress may play an important role in the development of insulin resistance in LPL heterozygous mice.